2015
DOI: 10.1155/2015/704382
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Cilastatin against Vancomycin-Induced Nephrotoxicity

Abstract: Vancomycin is a very effective antibiotic for treatment of severe infections. However, its use in clinical practice is limited by nephrotoxicity. Cilastatin is a dehydropeptidase I inhibitor that acts on the brush border membrane of the proximal tubule to prevent accumulation of imipenem and toxicity. The aim of this study was to investigate the potential protective effect of cilastatin on vancomycin-induced apoptosis and toxicity in cultured renal proximal tubular epithelial cells (RPTECs). Porcine RPTECs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 39 publications
3
56
0
Order By: Relevance
“…The visualization of large amounts of vancomycin at the brush border also points to either ongoing secretion or reabsorption of the drug at the apical side (i.e., from the urine) 57, 58 . In support, recent preclinical data have demonstrated vancomycin transport across the brush border membrane by apical endocytosis via dehydropeptidase 59 and megalin 60 and vancomycin‐mediated inhibition of the expression and function of P‐glycoprotein, an efflux transporter 61 . Although mechanistically plausible, the involvement of the multidrug and toxin extrusion (MATE1 and MATE2‐K) family of proteins in the secretion of vancomycin has yet to be demonstrated.…”
Section: Mechanisms Of Vikimentioning
confidence: 66%
See 1 more Smart Citation
“…The visualization of large amounts of vancomycin at the brush border also points to either ongoing secretion or reabsorption of the drug at the apical side (i.e., from the urine) 57, 58 . In support, recent preclinical data have demonstrated vancomycin transport across the brush border membrane by apical endocytosis via dehydropeptidase 59 and megalin 60 and vancomycin‐mediated inhibition of the expression and function of P‐glycoprotein, an efflux transporter 61 . Although mechanistically plausible, the involvement of the multidrug and toxin extrusion (MATE1 and MATE2‐K) family of proteins in the secretion of vancomycin has yet to be demonstrated.…”
Section: Mechanisms Of Vikimentioning
confidence: 66%
“…As such, an increase in malondialdehyde levels and a decrease in antioxidative enzyme activities – reduced glutathione peroxidase and superoxide dismutase – as indicators of oxidative stress have been reported in the kidney tissue of rats treated with vancomycin; antioxidants, including a superoxide dismutase conjugate, 78 reversed or prevented these effects and downstream histopathologic damage. In addition, the superoxides produced cause mitochondrial membrane depolarization and subsequent release of cytochrome C with activation of downstream caspases 59, 82 , ultimately leading to cell apoptosis.…”
Section: Mechanisms Of Vikimentioning
confidence: 99%
“…In experimental animals, coadministration (or pretreatment) of rats with antioxidative compounds that express superoxide dismutase attenuated proximal renal tubular injury with a favorable histological outcome [Oktem et al 2005;Nishino et al 2003]. Superoxide production by vancomycin causes depolarization of mitochondrial membrane potential with a release of cytochrome C, and a subsequent activation of both caspases 9 and 3 [Arimura et al 2012;Humanes et al 2015]. The latter is involved in apoptotic cell death.…”
Section: Mechanisms Of Vancomycin-induced Nephrotoxicitymentioning
confidence: 99%
“…These therapeutic agents enhance the survival of renal tubular cells by reducing DNA fragmentation, apoptosis and necrosis; and in certain instances by the modulation of autophagy [Huang et al 2016]. Nevertheless, in contrast to the effect of cilastatin previously discussed, it is unclear if antioxidative strategy would place a limitation on the bactericidal activity of vancomycin [Humanes et al 2015]. Clinical trials are therefore needed to validate the renal protective advantage of these agents in the human population.…”
Section: Antioxidative Therapymentioning
confidence: 99%
“…Several antioxidants including: vitamin E (8), 2, 3-dihydroxybenzoic acid (9), curcumin (10) and vitamin C (11) have been reported that reduces VIN. Based on these data, renal tubular ischemia due to the oxidative effects of VCM is the main known mechanism of VIN (5,12,13). ditional medicine, the leaves of the plant are widely used as diuretic, expectorant, blood purifier, hypoglycemic, and odontolgic (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%